2019
DOI: 10.5539/hes.v9n4p58
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Effect of Social Achievement Goals and Classroom Incivility on Difficulties during Emotion Regulation

Abstract: The aim of this study is to examine the predictive role of students’ social achievement goals and classroom incivility levels in their emotion regulation skills. The study was conducted with 309 university students and used “Social Achievement Goal Scale”, “The Difficulties in Emotion Regulation Scale” and “Classroom Incivility Scale” as data collection tools. The study was carried out with 309 university students in Turkey during 2016-2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The finding is consistent with previous studies that males have higher levels of moral disengagement and classroom incivility than females (Caprara et al, 2014; Spadafora & Volk, 2021; Wang, Ryoo, et al, 2017). The probable reason is that female adolescents have more moral emotions (e.g., guilt and empathy) and greater effortful control to limit their engagement in classroom incivility than male adolescents (Georgiou et al, 2021; Turhan et al, 2019). Similarly, multigroup analyses also showed that early and middle adolescents have different mechanisms underlying the mediation model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding is consistent with previous studies that males have higher levels of moral disengagement and classroom incivility than females (Caprara et al, 2014; Spadafora & Volk, 2021; Wang, Ryoo, et al, 2017). The probable reason is that female adolescents have more moral emotions (e.g., guilt and empathy) and greater effortful control to limit their engagement in classroom incivility than male adolescents (Georgiou et al, 2021; Turhan et al, 2019). Similarly, multigroup analyses also showed that early and middle adolescents have different mechanisms underlying the mediation model.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents establish higher social network positions by engaging in moderate levels of classroom incivility (Spadafora et al, 2021). However, some studies indicate that classroom incivility can lead to many negative consequences for adolescents, such as psychological distress, disengagement from lessons, dissatisfaction with institutions, performance decline, and serious antisocial behaviors (Caza & Cortina, 2007; Farrell et al, 2016; Hudgins et al, 2022; Spadafora et al, 2020, 2021; Turhan et al, 2019). Most importantly, low‐intensity negative behaviors can be contagious (Foulk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%